HUBUNGAN PENINGKATAN PENGETAHUAN PEDOMAN GIZI SEIMBANG MELALUI MEDIA SOSIAL INSTAGRAM TERHADAP REMAJA UMUR 18 - 24 TAHUN - Fatimah Anggraini, (2020)
Indonesia experiences a double nutritional burden, where malnourished people continue to increase and have not yet been completely dealt with in the meantime, communities with more nutrition are starting to increase. The lack of knowledge of a person will affect the problem of balanced nutrition. Balanced nutrition is a daily food composition that contains nutrients in the amount and type that suits the needs of a person's body by paying attention to food diversity, physical activity, clean living behavior and pay attention to normal weight to prevent nutritional problems. This research was to find out about relationship between increasing knowledge of balanced nutrition guidelines (food diversity, clean and healthy life behavior, physical activity, and maintaining normal weight) through social media Instagram for adolescents aged 18-24 years. This research was quantitative and uses cross sectional design. The research sample consisted of 67, Fatimah was using Instagram social media accounts following as a purposive sampling technique. Media information used in this study was Instagram, and data collection was collected using Google form questionnaire. Based on the Wilcoxon test results showed an association of increased knowledge of balanced nutrition guidelines after nutrition knowledge intervention through social media Instagram (P = 0.000). There is a relationship of increasing knowledge of balanced nutrition guidelines (food diversity, clean and healthy life behavior, physical activity, and maintaining normal weight) through social media Instagram for adolescents aged 18-24 years.